Complete genome sequence of burkholderia gladioli Phage Maja - Yu, Zihao (2021)
Burkholderia gladioli is a Gram-negative bacterium associated with cystic fibrosis infections. Here, we describe the genome sequence of B. gladioli phage Maja. Maja is most related to another Burkholderia phage, BcepF1, and may be a temperate phage, despite the absence of repressor or integrase homologs in its genome sequence.